The Relationship Between Pagan Fate and Christian Grace in the Thought of Józef Tischner - Lech Wołowski (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
This article examines one of the greatest contributions of Józef Tischner to the area of anthropology and charitology by analyzing, in a systematical way, his original thought regarding the relationship between the pagan concept of fate (fatum) and the Christian concept of grace (charis). The originality of this contribution concerns three main areas. The first one concerns the historical-charitological aspect in which Tischner proposes a new approach which helps him to emphasize the personalistic aspect of grace. Instead of considering the problem form a typical intra-Christian perspective, he approaches the concept of grace by confronting it with the historical, pagan concept of impersonal fate. Secondly, he brings to the light an ancient Greek idea of the aesthetic overcoming of the tragic defeat caused by fate, and by showing its insufficiency, he discovers and demonstrates the depth, beauty and hidden ultimate power of the aesthetic dimension of Christian grace. Finally, he argues that the problem of the relationship between fate and grace is not an issue of the ancient past, but constitutes the core of one of the greatest contemporary challenges faced by modern Christian society: the ever growing wave of neopaganism.